Soybean diseases: biology, identification, control and management: IITA research guide, No. 40 - Akem, C. (1991)
More than 100 pathogens attack soybean, but only a third of them are of economic importance. Common yield reductions vary between 10% and 30%. Soybean diseases are caused by viruses, bacteria, fungi, and nematodes. Disease management is based on several control principles that should be preferably combined in an integrated pest management approach.